Effects of nitrogen and sulphate addition on methane oxidation in the marsh soil of a typical subtropical estuary (Min River) in China. Issue 7 (9th August 2018) - Hu, Minjie; Wilson, Benjamin J.; Sun, Zhigao; Huang, Jiafang; Tong, Chuan
ABSTRACT: Methane (CH4 ) oxidation plays an important role in regulating the atmospheric CH4 balance. Although nitrogen (N) enhancement and sulphate ( ) deposition are major environmental problems facing the Min River estuary in subtropical China, the interactive effects of N and on CH4 oxidation remain poorly understood. We conducted an incubation experiment to investigate the effects of N and additions on CH4 oxidation in marsh soils. CH4 oxidation exhibited distinct seasonal variations, which correlated with changes in temperature and soil moisture; in addition, CH4 oxidation rates were enhanced by the addition of nitrate ( ), but were slightly inhibited by the addition of ammonium ( ) and . The combined effects of N and on CH4 oxidation were controlled primarily by the form of N, which may imply that inhibition of CH4 oxidation with addition may be counteracted by N addition, especially in estuarine marsh soils with low N and high concentrations. We propose that, although was more effective in stimulating CH4 oxidation and the inhibition caused by and was minor, CH4 oxidation may be inhibited because was dominant and accompanied by strong deposition in the Min River estuary. As such, future CH4 emissions from estuarine wetlands may increase as a result of higher inputs of and .